Individual, work-related and organizational factors influencing adherence to standard precautions - Avelar, Thaís de Sousa; Santos, Luiza Maria dos; Araújo, Layane Cristina; Moraes, Juliano Teixeira; Dias, Ana Angélica Lima (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Standard Precautions (SP) are a set of prevention practices that should be applied to all patients. Aim: To identify individual, work-related and organizational factors that influence adherence to SP among nursing professionals in a hospital in Minas Gerais. Outlining: Cross-sectional, quantitative study using the instrument Psychosocial and Organizational Factors that Influence Adherence to PP with 10 psychometric scales Likert type. Descriptive and correlational analyses were performed. Results: The consistency of the instrument was 0.86. The scales presented means with intermediate score. The highest average was the scale “Training in prevention of occupational exposure to HIV” (4.6) and the lowest were “Obstacles to follow SP” (3.9) and “Availability of Personal Protective Equipment (PPE)” (3.8). There was a strong correlation between “Safety Climate” and “Availability of PPE” (r = 0.719). Implications: Training is essential for adherence to SP; however, it is necessary to identify the other factors that influence this practice.